Athanasius Kircher – The Multifold One and His Contradictions (KULT_online, 2010)
The famous polyhistor of the 17th century, Athanasius Kircher (1601/2-1680), is in demand, considering the number of research projects on him. His manifoldness is reflected in the disciplines that are interested in Kircher: linguistics, musicology, historiography, theology, art history, and others. By publishing this edition of his autobiography and its translations, the Romanist scholar Giunia Totaro offers this field of study a central source of insight into Kircher's character. The Vita of Kircher was previously difficult to access and hardly studied critically. With her book, Totaro provides a comprehensive basis for further studies. Moreover, a sound research overview, the critical discussion of some parts of the Vita, and the extensive bibliography enrich the volume.